West versus East Mediterranean Sea: origin and genetic differentiation of the sea cucumber Holothuria polii - Valente, Sara (2016)
We studied the genetic structure of the sea cucumber Holothuria (Roweothuria) polii (Delle Chiaje 1823) by analysing the mitochondrial DNA variation in two fragments of cytochrome oxidase I (COI) and 16S genes. Individuals were collected in seven locations along the Mediterranean Sea, which cover a wide range of the species distribution. We found high haplotype diversity for COI and moderate diversity for 16S, and low nucleotide diversity for both genes. Our results for the COI gene showed many recent and exclusive haplotypes with few mutational changes, suggesting recent or ongoing population expansion. The Western and Eastern Mediterranean populations exhibited slight but significant genetic differentiation (COI gene) with higher genetic diversity in the East. The most ancient haplotype was not present in the westernmost sampling location (SE Spain). The oldest expansion time was observed in Turkey, corresponding to mid-Pleistocene. Turkey had also the highest genetic diversity (number of total and exclusive haplotypes, polymorphisms, haplotype and nucleotide diversity). This suggests that this region could be the origin of the subsequent colonizations through the Mediterranean Sea, a hypothesis that should be assessed with nuclear markers in future research.